Perkembangan penelitian penyakit jantung koroner: analisis bibliometrik terhadap faktor risiko dan kepatuhan pengobatan - Budihardjo, Rosavelina Sintaasih (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Coronary heart disease (CHD) is a leading cause of death globally, with risk factors such as hypertension, diabetes, smoking, and unhealthy lifestyle. Treatment adherence is a crucial aspect in CHD management, influenced by age, family support, and self-efficacy. Purpose: To contribute to a deeper understanding of risk factors, medication adherence, and their impact on the quality of life of CHD patients, and to map the development of research in this field over the past decade. Methods: This study uses a bibliometric approach to analyze research trends related to CHD, risk factors, and medication adherence based on scientific publications in the last decade (2014-2024). Data were collected through Publish or Perish and analyzed using VOSviewer to map publication patterns by year, country, publisher, article type, and keyword analysis. Results: Publications surged in 2014–2015, plateaued in 2016–2018, and declined sharply in 2019–2020, likely due to the COVID-19 pandemic. The United States and Australia dominate publications, with Elsevier, academic.oup.com, and Springer as the main publishers. Research articles outnumber literature reviews.